Origins of Possession : Owning and Sharing in Development - Rochat, Philippe (Cambridge : Cambridge University Press, 2014)
Human possession psychology originates from deeply rooted experiential capacities shared with other animals. However, unlike other animals, we are a uniquely self-conscious species concerned with reputation, and possessions affect our perception of how we exist in the eyes of others. This book discusses the psychology surrounding the ways in which humans experience possession, claim ownership, and share from both a developmental and cross-cultural perspective. Philippe Rochat explores the origins of human possession and its symbolic development across cultures. He proposes that human possession psychology is particularly revealing of human nature, and also the source of our elusive moral sense.
Title from publisher's bibliographic system (viewed on 08 Oct 2015).
Keywords: Possessiveness